Durs Grünbein’s Lob des Taifuns: Images and city figures of Japan (Itinera, 2020)
This paper aims to analyse the “Lob des Taifuns. Reisetagebücher in Haikus” by Durs Grünbein, with the intention of showing how Japanese theories of thought, poetic and artistic practises – in particular, haikus – have played a decisive role for Grünbein, not only for understanding “another culture”, but also for reflecting on the aesthetic experience and the forms of telling proper to the metropolitan setting. In this perspective, Grünbein’s book becomes an “ideal place” to see the dialogue between “East” and “West” as an establishment of a tension-filled space between different styles which, without denying their own specificity, offer themselves to contamination and give life to the most recent form of the “metropolitan aesthetic”.
Keywords: German poetry, metropolitan experience, forms of telling, haiku